KOMPARASI AKIBAT TIDAK TERCATATNYA PERKAWINAN INDONESIA DAN PAKISTAN: STUDI REFORMASI HUKUM INDONESIA PERSPEKTIF MASLAHAH MURSALAH: Studi Reformasi Hukum Indonesia Perspektif Maslahah Mursalah - Moh. Umar Fadlil; Abd. Rouf (Program Studi Hukum Keluarga (Ahwal Syakhshiyah), 2026)
Unregistered marriages are an important issue in contemporary Islamic family law because they have a direct impact on the protection of the rights of husbands, wives, and children. In Indonesia, this practice still occurs due to the separation between the validity of marriage according to religion and the state's obligation to register it, thus creating legal uncertainty and weak protection of family rights. In contrast, Pakistan implements stricter marriage registration regulations through the Muslim Family Laws Ordinance (MFLO) 1961, accompanied by legal sanctions, which are more effective in maintaining order and protecting family law. This study aims to compare the legal consequences of unregistered marriages in Indonesia and Pakistan and formulate their implications for Indonesian marriage law reform from the perspective of maslahah mursalah. Through the perspective of maslahah mursalah, this research aims to formulate a normative basis and recommendations for reforming Indonesian marriage law so that marriage registration is not merely positioned as an administrative obligation, but as a legal mechanism that guarantees the welfare, justice, and protection of vulnerable parties within the family. The method used is normative legal research with a comparative and conceptual approach through a literature study. The results of the study show that the absence of registration and strict sanctions in Indonesia weakens the protection of the rights of wives and children, while the Pakistani system better guarantees legal certainty. This study emphasizes the need to strengthen marriage registration regulations in Indonesia in order to achieve justice, legal certainty, and family welfare.